Gerlach and Ely’s Learning Model: How to Implement It to Online Learning for Statistics Course - Agus Miftakus Surur (Edumatika : Jurnal Riset Pendidikan Matematika, 2021)
Statistics is a compulsory subject that is very useful for students, so, in online learning, lecturers need to determine a suitable learning model. Lecturers can apply specific learning models that are adapted to the situation. The existence of characters in Gerlach and Ely's complete learning model can be a choice for lecturers in carrying out their learning so that even though learning is carried out online, the needs needed by students are still met. The purpose of the research is to describe the design of the Gerlach and Ely learning model, which is carried out online in the statistics course. The research method is field research with data obtained through observational studies of the learning process, interviews with students taking Statistics courses, and documentation of the learning process and the results of student assignments. The data analysis used Spradley Model. The results of this study are that students and lecturers can do online learning by maximizing some of the available applications with improvements to the media used. The media must be easily accessible to support fluency when learning. The lecturer prepares all the learning needs in the stages of Gerlach and Ely's learning activities. The advantages of this applied model are that it provides detailed stages in learning to determine learning objectives to the analysis stage of the results of the feedback provided by students. It can guide learning to achieve the objectives of the planned learning. The details of Gerlach and Ely's learning model need to be emphasized so that all stages can be carried out according to the systematics in its application.